Neuromuscular responses to combined neuromuscular electrical stimulation and motor control exercises in a patient with recurrent low back pain: A single subject research report - Wattananon, Peemongkon; Songjaroen, Sranya; Sungnak, Panakorn; Richards, Jim (Physiotherapy theory and practice, 2024)
Previous studies have demonstrated changes in lumbar multifidus muscle (LM) contractility after motor control exercises (MCE), and it has been hypothesized that adding neuromuscular electrical stimulation (NMES) may help to re-activate motor units. To present the effects of combined NMES and MCE on LM contractility, spatial and temporal motor unit recruitment, and movement control in a patient with recurrent low back pain (rLBP). Motion tracking system was used to measure quality of movement (smoothness) during an active forward bend, while ultrasound imaging and decomposition electromyography were used to measure the LM contractility and motor unit recruitment during the Sorensen test. These data were collected pre and post intervention. Perceived improvement was also recorded. Improved movement smoothness post intervention was found, with increases in LM contractility from 68.1% to 97.7%, and from 74.2% to 86.7% on the right and left sides, respectively. Number of motor unit increased from 14 to 18 units, while mean firing rate decreased from 10.9 to 7.1 pulses/second post intervention. The patient also reported a perceived improvement of +2 on the Global Rating of Change (GROC). However, this change was not greater than +3 to be considered as minimal clinically important difference. These findings indicate improvements in movement control, LM contractility, and changes in spatial and temporal motor unit recruitment in the study patient, suggesting the potential clinical utility and the need for further research on combined NMES and MCE in the treatment of patients with rLBP.